A phase 1 clinical trial of vorinostat in combination with decitabine in patients with acute myeloid leukaemia or myelodysplastic syndrome. (8th July 2014) - Kirschbaum, Mark; Gojo, Ivana; Goldberg, Stuart L.; Bredeson, Christopher; Kujawski, Lisa A.; Yang, Allen; Marks, Peter; Frankel, Paul; Sun, Xing; Tosolini, Alessandra; Eid, Joseph E.; Lubiniecki, Gregory M.; et al.
Summary Patients with acute myeloid leukaemia (AML) or myelodysplastic syndrome (MDS) may respond to treatment with epigenetic‐modifying agents. Histone deacetylase inhibitors may synergize with hypomethylating agents. This phase 1 dose‐escalation study was designed to determine the maximum tolerated dose, recommended phase 2 dose, safety and tolerability of vorinostat plus decitabine in patients with relapsed/refractory AML, newly‐diagnosed AML, or intermediate‐ to high‐grade MDS. Thirty‐four patients received concurrent therapy with decitabine plus vorinostat and 37 received sequential therapy with decitabine followed by vorinostat. Twenty‐nine patients had relapsed/refractory AML, 31 had untreated AML and 11 had MDS. The target maximum administered dose (MAD) of decitabine 20 mg/m2 daily for 5 d plus vorinostat 400 mg/d for 14 d was achieved for concurrent and sequential schedules, with one dose‐limiting toxicity (Grade 3 QTc prolongation) reported in the sequential arm. Common toxicities were haematological and gastrointestinal. Responses were observed more frequently at the MAD on the concurrent schedule compared with the sequential schedule in untreated AML (46% vs. 14%), relapsed/refractory AML (15% vs. 0%) and MDS (60% vs. 0%). Decitabine plus vorinostat given concurrently or sequentially appears to be safe and well‐tolerated. Concurrent therapy shows promising clinical activity in AML or MDS, warranting further investigation.